Indication for an additional postoperative antibiotic treatment after surgical incision of serious odontogenic abscesses. Issue 3 (March 2020) - Böttger, Sebastian; Lautenbacher, Katharina; Domann, Eugen; Howaldt, Hans-Peter; Attia, Sameh; Streckbein, Philipp; Wilbrand, Jan-Falco
Abstract: Introduction: Serious abscesses of an odontogenic origin occur frequently in the oral and maxillofacial surgery departments. Rapid surgical incision and drainage constitutes the most important therapeutic action. However, additional surgical therapy and supplementary administration of antibiotics is often carried out, such that the efficiency of this supplementary therapeutic option has been questioned. Methods: All patients with severe odontogenic infections who received surgical treatment under general anaesthesia were recruited to this retrospective study. We determined whether they received additional antibiotic therapy on the ward and if it was possible to improve therapeutic outcomes using this option. Results: A total of 258 patients with a severe odontogenic infection between January 2008 and August 2014 were included. The most frequent infection observed was a submandibular abscess (56%), followed by a perimandibular abscess (18%) and a submental abscess (9%). About 65% of the patients were treated with antibiotics in addition to surgery. The median CRP level prior to surgical treatment was 87.8 mg/l (Q1 : 40.3 mg/l; Q3 : 143.5 mg/l) in patients who were administered an additional antibiotic and 83.8 mg/l (Q1 : 37.3 mg/l; Q3 : 135.0 mg/l) in those who received no antibiotic treatment after surgery. The postoperative median CRP levels were 116.5 mg/l (Q1 : 52.1 mg/l; Q3 : 159.3 mg/l) and 106.5 mg/l (Q1 : 40.6 mg/l; Q3 : 152.6 mg/l), respectively. Neither the preoperative CRP level (p = 0.546) nor the postoperative CRP level (p = 0.450) differed significantly between the groups. But patients who received additional antibiotic therapy had a significantly longer hospital stay (median: 6 days; range: 1–22 days) than patients who had no additional antibiotic therapy (median: 4 days; range: 1–19 days) (p = 0.002). Conclusions: This study did not show an improvement in the therapeutic outcome with administration of supplementary antibiotics in addition to surgery. Thus, surgically incising an abscess is the most important therapeutic action and administration of antibiotics must be critically scrutinised.